2020
DOI: 10.1002/celc.202000788
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Quercetin and Carbendazim in Wine Samples Using Disposable Electrochemical Sensors

Abstract: Developing low‐cost and fast methods for on‐site analysis is a long‐sought goal of the wine industry, especially to detect excessive concentrations of naturally occurring compounds such as polyphenols and pesticide residues. In this paper, we report on the treatment of screen‐printed electrodes, which were capable of detecting the flavonoid quercetin and the pesticide carbendazim simultaneously in wine samples with limits of detection of 51.8×10−9 mol L−1 and 60×10−9 mol L−1, respectively. Furthermore, no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It is worth mentioning that electrochemical methods, including among others voltammetry, offer a high sensitivity with relatively low-cost instrumentation and analysis [ 4 ]. In turn, due to the mass production nature, availability and low cost of screen-printed electrodes, they are now a good approach to the preparation of voltammetric sensors [ 5 , 6 , 7 , 8 , 9 ]. Moreover, the application of nanomaterials together with screen-printing fabrication is a very actual subject of research of particular importance especially for environmental monitoring and medical diagnostics, but also in other fields of analytical applications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that electrochemical methods, including among others voltammetry, offer a high sensitivity with relatively low-cost instrumentation and analysis [ 4 ]. In turn, due to the mass production nature, availability and low cost of screen-printed electrodes, they are now a good approach to the preparation of voltammetric sensors [ 5 , 6 , 7 , 8 , 9 ]. Moreover, the application of nanomaterials together with screen-printing fabrication is a very actual subject of research of particular importance especially for environmental monitoring and medical diagnostics, but also in other fields of analytical applications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pretreatment produces an increase in the number of electroactive carbons on the surface, thus increasing the sensitivity toward hydroquinone, catechol and bisphenol A as depicted in Figure 1D. The pretreated flexible SPE could be stored under ambient conditions for 30 days with an average decrease of 10% in the initial current value [20,31]. All subsequent experiments were performed with SPEs electrochemically pretreated with a sulfuric acid solution and using chronoamperometry.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative to these high-cost methods is to employ electrochemical sensors whose sensitivity, portability, fast response, and low cost [15,17] have been exploited in monitoring the environment [18] and food processing [19,20], in addition to medical diagnosis [21]. These sensors can be made with a variety of materials, including quantum dots, composites containing metal nanoparticles, carbon-based materials and aptamers [15].…”
Section: Introductionmentioning
confidence: 99%
“…6C, screen-printed carbon electrodes were utilized to detect excessive concentrations of naturally occurring polyphenols and pesticide residues, namely the flavonoid quercetin and the pesticide carbendazim simultaneously in wine samples with a LOD of 60 nM reported for carbendazim. 58 The authors found that the use of an electrochemical pre-treatment through chronoamperometric experiments at a potential fixed of +1.2 V for 5 min in a saturated solution of sodium bicarbonate solution eliminated residues and impurities from the homemade carbon ink comprising graphite and alkyd resin eventually deposited on the electrodes. 58 The authors applied their sensor to the simultaneous detection of quercetin and carbendazim within white and red white observing 90–114% recoveries.…”
Section: Electroanalytical Based Sensors For the Simultaneous Detecti...mentioning
confidence: 99%